"Yopilano" Method (Yoga, Pilates, And Hypnotherapy) exercise: Association of labour and childbirth - Christina Roos Etty; Surya Anita; Julia Siahaan; Rut Enjelika (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The normal labor process is often influenced by psychological and physical factors in pregnant women. The YOPILANO method (Yoga, Pilates, and Hypnotherapy) is believed to enhance relaxation, strengthen pelvic muscles, and improve mental readiness to support normal delivery. Purpose: To determine the effect of implementing the YOPILANO method on the likelihood of normal delivery among third-trimester pregnant women. Method: A descriptive quantitative with quasi-experimental specially focusing on case control group. The study took place from June to October 2025 in Deli Serdang, Medan. The independent variables studied were yoga, pilates, and hypnotherapy, while the dependent variable was labour and childbirth. Using purposive sampling and taro yamene formula 24 participants were selected divided into 2 group included case and control group, who meet specific inclusion and exclusion criteria. The analysis proceeded with a univariate test to determine the frequency distribution of respondent’s characteristics, followed by bivariate analysis using chi-square test. Results: The control group, most participants did not receive the yopilano intervention, namely 8 people (66.7%). The Chi-square test results show a p-value of 0.040, which means that there is a statistically significant relationship between the practice of Yopilano and the occurrence of normal delivery at a significance level of 5% (p < 0.05). Conclusion: Pregnant women who follow the yopilano practice have a greater chance of experiencing normal delivery compared to pregnant women who do not follow the practice. A value of 6.0 for the crude odds ratio (OR) indicates that pregnant women who practice yopilano are six times more likely to experience normal delivery than those who do not practice yopilano.